Estudo da associação entre a presença do anticorpo contra o peptídeo citrulinado cíclico e os índices de atividade de doença, de capacidade funcional e de dano estrutural, medido através da radiografia convencional e da ressonância magnética, na artrite reumatoide estabelecida - Lilian Santuza Santos Porto (2014)
Introduction: The presence of anti-cyclic citrullinated peptide (anti-CCP) is an important diagnostic and prognostic tool for rheumatoid arthritis (RA). The relation between disease activity and functional capacity was also studied. Objectives: To evaluate the relation between the presence of anti-CCP and indices of disease activity, functional capacity and structural damage indices, as measured by means of conventional radiography (CR) and magnetic resonance imaging (MRI) in a group of Brazilians with established RA. Methods: A cross-sectional study was carried out on patients diagnosed with RA and with one to ten years of symptons. The participants underwent clinical examination and were given the anti-CCP test. Disease activity was measured by the Clinical Disease Activity Index (CDAI), and functional capacity was estimated by the Healthy Assessment Questionnaire (HAQ). The CR analysis of the hands was carried out by the Sharp index modified by van der Heijde (SmvH) and the MRI analysis of the dominant hand by the Rheumatoid Arthritis Magnetic Image Scoring (RAMRIS). Results: Fifty-six patients were evaluated. Their median and interquartile interval (IIq) age was 55 (47.5-60) years, with women comprising 89.3% of the participants. Thirty-seven (66.1%) patients were anti-CCP positive and twenty-five (44.7%) were smokers or ex-smokers. The median (IIq) of the interval between inception of the symptoms and diagnosis was 0 (0-1). The medians (IIq) CDAI and HAQ were 14.75 (5.42-24.97) and 1.06 (0.28-1.75), respectively. Forty-one percent were in remission or had low disease activity. Image evaluation found a SmvH median (IIq) of 2 (0-8) and a RAMRIS median (IIq) of 15 (7-35). No association was found between the anti-CCP and the CDAI, HAQ or with the damage scores SmvH and RAMRIS. Conclusion: Our results did not establish any relation between the anti-CCP and the disease severity, measured by disease activity, functional capacity and joint damage indices, even when analyzed by MRI. Early diagnosis and appropriate response to therapeutic intervention could have contributed to the formation of a group of persons with less severe and less erosive disease. With these results, a lower influence of anti-CCP on the prognosis of patients with more favorable disease profile was raised. At the present moment we cannot recommend the anti-CCP as a prognostic tool in established RA.